ಬೀದರ ಜಿಲ್ಲೆಯ ತತ್ವಪದಕಾರರ ಸ್ಮಾರಕಗಳು-ಸಂಪುಟ ೩ - (:unkn) unknown (Gulbarga University, 2011)
This book is an collection of Research Articles on Tatvapadakara's life and Monuments of Bhalki and Humnabad of Bidar Distrcits
Bidar Jilleya Tatva Padakarara Smarakagalu Vol-3
Keywords: Kannada; History; Kannada; Kannada